Pengaruh Pola Asuh Orang Tua Dan Kesadaran Diri (Self Awareness) Terhadap Kedisiplinan Peserta Didik Di Sekolah Menengah Pertama Swasta Insan Teratai Tangerang - Bayu Sukma; Ghana Yoga Mahardika (Jurnal Pendidikan, Sains, Sosial dan Agama (Dharma Edukasi), 2025)
Discipline is an important aspect of education because it not only shapes students' character but also contributes to academic achievement and the creation of a conducive learning environment. The phenomenon at SMPS Insan Teratai Tangerang shows that the level of student discipline is still low, with only 44.25% classified as highly disciplined, while the other 55.75% have not yet demonstrated optimal disciplinary behavior. This condition prompted a study to examine the extent to which parenting patterns and self-awareness influence student discipline. This study used a descriptive quantitative approach involving 73 respondents selected through purposive sampling. The instrument used was a Likert scale questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression through SPSS version 25. The results showed that parenting styles had a significant effect on discipline, as did self-awareness, which was proven to have a positive influence. Simultaneously, both variables contribute significantly to the formation of student discipline. These findings emphasize the importance of synergy between appropriate parenting and the development of self-awareness in supporting educational success through the formation of a disciplined character.